Penalty Method for a Class of Differential Hemivariational Inequalities with Application. (27th July 2021) - Faiz, Zakaria; Baiz, Othmane; Benaissa, Hicham; El Moutawakil, Driss
Abstract: In this paper, we consider a penalty method for a class of differential hemivariational inequalities in reflexive Banach spaces, governed by a set of constraints. First, we recall the existence and uniqueness result of the differential hemivariational inequality. Further, we introduce a penalized problem without constraints and we prove that, as a penalty parameter tends to zero, the solution of the original inequality can be approached to the solution of the penalized problem. Finally, we illustrate our results by an example of a contact problem for which our abstract results can be applied.